Optimal Sequential Delegation - Eugen Kovác; Daniel Krähmer (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2013)
The paper extends the optimal delegation framework pioneered by Holmström (1977, 1984) to a dynamic environment where, at the outset, the agent privately knows his ability to interpret decision relevant private information received later on. We show that any mechanism can be implemented by a sequential menu of delegation sets where the agent first picks a delegation set and then chooses an action within this set. For the uniformquadratic case, we characterize when sequential delegation is strictly better than static delegation and derive the optimal delegation menu. We provide sufficient conditions so that our results extend beyond the uniform distribution.
urn:nbn:de:bvb:19-epub-17331-9
Keywords: D02; D20; D82; D86; 330; optimal delegation; sequential screening; dynamic mechanism design; non-transferable utility